Evaluation of potential probiotic Bacillus velezensis FS26 against aquaculture pathogens and its ability to utilise prebiotics from Arthrospira platensis A1 - Sam-on, Muhamad Firdaus Syahmi (2023)
Pathogenic bacteria such as Vibrio spp. and Aeromonas spp. frequently cause detrimental effects on aquaculture production. Antibiotics were previously utilised to treat infections, but this led to antibiotic-resistant bacteria emerging in the environment. Probiotics and prebiotics were introduced to boost the host's microbiota, disease protection, health condition, growth efficiency, feed consumption, stress response and overall vigour. Synbiotic is another approach that should be evaluated intensively to solve the infections problems. However, probiotic bacteria need to show the ability to utilise prebiotic for synbiotic preparation. Therefore, this study aims to evaluate the potential probiotic of selected bacteria against aquaculture pathogens and capability to use prebiotic from Arthrospira platensis A1. Bacillus velezensis FS26 (Genome accession number: JAOPEO000000000; 16S rRNA accession number: MZ960133) was isolated from giant freshwater prawn and showed good probiotic properties against pathogens in aquaculture through in vitro and in silico studies. Agar well diffusion assay exhibited the capability of this bacterium through diameter of inhibition against the pathogenic Aeromonas hydrophila LMG13658, A. veronii clone DK-A.veronii-27, Vibrio campbellii PKGL21, V. alginolyticus PKS15, V. parahaemolyticus PKK24 at 23.7, 25, 30, 13.3 and 12.3 mm, respectively. This bacterium is regarded as harmless based on susceptibility towards 13 antibiotics, γ-haemolytic activity in blood agar and in silico prediction for the lack of 96 antibiotic resistance genes, pathogenic genes and virulence factors. Additionally, B. velezensis FS26 has shown the capability to utilise commercial prebiotics such as lactulose, raffinose and inulin through in silico and in vitro investigation. The bacterial genome predicted six enzymes that could hydrolyse glycosidic bonds in prebiotics, such as α-galactosidase, invertase, endolevanase, β-2,6-fructan-6-levanbiohydrolase and levansucrase. Moreover, using prebiotics from aquaculture sources such as microalgae could enhance the palatability of the synbiotic. Hence, water-soluble nondigestible polysaccharide was extracted from Arthrospira platensis A1 as a prebiotic for B. velezensis FS26. The structure of water-soluble polysaccharides demonstrated the presence of α-glycosidic bonds at wavelength 860 nm and water-soluble compounds at wavelength between 300 to 400 nm through FTIR and UV-VIS spectroscopy analysis. In the outcome, water-soluble nondigestible polysaccharide extracted using autoclave exhibited a promising prebiotic activity towards potential probiotic B. velezensis FS26 by significantly enhance the bacterial growth on enriched and minimal media at 0.6 x 109 CFU/mL and 7.1 x 109 CFU/mL, compared to control. In conclusion, the findings demonstrate the capability of probiotic B. velezensis FS26 to inhibit the aquaculture pathogens and utilise prebiotic from A. platensis A1.